Sosialisasi pendidikan anti korupsi yang berintegritas di SMK Negeri 02 Mei Bandar Lampung - Yunisca Nurmalisa; Nurhayati; Hermi Yanzi; Devi Sutrisno Putri (Jurnal Sumbangsih, 2022)
Implement anti-corruption in oneself, especially for teachers. Integrity in implementing anti-corruption education within oneself and the environment will be one of the solutions in responding to social problems that occur in society and will increase civic disposition as an Indonesian citizen. Through the soft skills approach, it is hoped that teachers and students at SMK Negeri 2 Mei Bandar Lampung can have a high integrtas to deal with corruption problems that occur daily in this global era. This activity method includes socialization activities to teachers of SMK Negeri 02 Mei Bandar Lampung. In the first stage, an analysis was carried out related to the problems experienced in the application of anti-corruption education in schools outside the learning materials. In the second stage, service activities will be carried out in the form of socialization. The participants of this activity are teachers of SMK Negeri 2 Mei Bandar Lampung. The implication of this service is that it can optimize soft skills, especially related to the integrity of teachers and students in implementing anti-corruption both in school and in daily life, with the hope that a good character will be formed, especially in preventing corruption from an early age.